Results of weed surveys for different land uses - Schöphen, Eszter; Tóth, Zoltán (GEORGIKON FOR AGRICULTURE, 2025)
Different land use patterns have a significant impact on the weed flora of agricultural land. Tillage, fertilisation and crop rotation have an important role to play in reducing weed infestation.  The effects of conventional ploughing and reduced tillage (min-till) on weed control in maize fields were investigated in a maize-wheat biculture with different nitrogen application rates in a long-term Soil Tillage field Experiment set up in Keszthely, Hungary in 2023 and 2024. The results showed that either tillage or fertilizer use had an effect in minimizing weed infestation.
Keywords: tillage; min-till; fertilizer; maize; weed cover